Tunable Förster resonance energy transfer in colloidal nanoparticles composed of polycaprolactone-tethered donors and acceptors : enhanced near-infrared emission and compatibility for in vitro and in vivo bioimaging - Yang, Cangjie (2020)
A near-infrared (NIR) fluorescent donor/acceptor (D/A) nanoplatform based on Förster resonance energy transfer is important for applications such as deep-tissue bioimaging and sensing. However, previously reported D/A nanoparticles (NPs) often show limitations such as aggregation-induced fluorescence quenching and poor interfacial compatibility that reduces the efficiency of the energy transfer and also leads to leaching of the small molecular fluorophores from the NP matrix. Here highly NIR-fluorescent D/A NPs with a fluorescence quantum yield as high as 46% in the NIR region (700–850 nm) and robust optical stability are reported. The hydrophobic core of each NP is composed of donor and acceptor moieties both of which are tethered with polycaprolactone (PCL), while the hydrophilic corona is composed of poly[oligo(ethylene glycol) methyl ether methacrylate] to offer colloidal stability and “stealthy” effect in aqueous media. The PCL matrix in each colloidal NP not only offers biocompatibility and biodegradability but also minimizes the aggregation-caused fluorescence quenching of D/A chromophores and prevents the leakage of the NIR fluorophores from the NPs. In vivo imaging using these NIR NPs in live mice shows contrast-enhanced imaging capability and efficient tumor-targeting through enhanced permeability and retention effect.